Health-related Quality of Life in Women with Cervical Cancer - Larissa Nascimento dos Santos; Luciana Castaneda; Suzana Sales de Aguiar; Luiz Claudio Santos Thuler; Rosalina Jorge Koifman; Anke Bergmann (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2019)
Abstract Objective To analyze the factors associated with health-related quality of life (HRQoL) in women with cervical cancer (CC) in a single center in Rio de Janeiro, state of Rio de Janeiro, Brazil. Methods A cross-sectional study in women with a diagnosis of CC followed-up in the gynecology outpatient clinic of the Hospital do Câncer II (HCII, in the Portuguese acronym) of the Instituto Nacional de Câncer (INCA, in the Portuguese acronym). The data were collected from March to August 2015. Women with palliative care, communication/cognition difficulty, undergoing simultaneous treatment for other types of cancer, or undergoing chemotherapy and/or radiation therapy were excluded. For the evaluation of the HRQoL, a specific questionnaire for women with CC was used (Functional Assessment of Cancer Therapy - Cervix Cancer [FACT-Cx]). The total score of the questionnaire ranges from 0 to 168, with higher scores indicating a better HRQoL. Results A total of 115 women were included in the present study, with a mean age of 52.64 years old (standard deviation [SD] = 12.13). The domains of emotional (16.61; SD = 4.55) and functional well-being (17.63; SD = 6.15) were those which presented the worst scores. The factors that had an association with better HRQoL in women with CC were having a current occupation, a longer time since the treatment and diagnosis, and women who had undergone hysterectomy. Conclusion Considering the domains of HRQoL of the women treated for cervical cancer, a better score was observed in the domains of physical and social/family wellbeing. For most domains, better scores were found between those with a current occupation, with a longer time after the diagnosis and treatment, and among those who had undergone a hysterectomy.